Dimensions of urban mobility cultures – a comparison of German cities - Klinger, Thomas; Kenworthy, Jeffrey; Lanzendorf, Martin (Elsevier, 2013)
In the context of the immense economic and social challenges urban transport faces in the near future, the analysis of city-specific differences in supply and usage of urban transport systems is a promising approach for identifying potential strategies for establishing more sustainable transport systems and mobility patterns. This study aims to address such differences by a comparative approach and is, to our best knowledge, the first one capturing the subjective dimension of urban mobility by integrating satisfaction and perception-related indicators at a city-level. Drawing on the socio-technical concept of urban mobility cultures, which combines socio-economic and urban form characteristics, mode-specific infrastructure supply, as well as the travel behaviour and underlying attitudes of a city’s inhabitants, we collected a set of 23 indicators from several sources, mainly from the early 2000s. These data have been applied to a sample of 44 German cities. As a result of a factor and cluster analysis we identified six groups of cities ranging from relatively mature and homogenous socio-technical settings, referred to as ‘cycling cities’ or ‘transit metropolises’, to rather less well-defined urban mobility cultures such as ‘transit cities with multimodal potential’, whose forthcoming development is not yet directed towards a specific future and, therefore, is open for political debate. The mismatch between objective and subjective indicators of urban mobility culture that has been shown for some city groups is another starting-point for changing urban mobility cultures in terms of taking people’s perceptions and evaluations of the local transport system more seriously.